2017
DOI: 10.2217/pme-2017-0065
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prenatal Testing: A Survey of Young (Future) Parents in Flanders

Abstract: The participants agreed nearly unanimously that NIPT must be offered to pregnant women with an increased risk of having a child with a genetic disorder, but they were also positive about extending NIPT screening to all pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…They were interested in FWGS for diseases that develop shortly after birth or during childhood and that are preventable or treatable. Our findings resonate with those from other studies showing that participants were favorable towards testing for childhood-onset conditions, whether or not performed through FWGS [21,[34][35][36].…”
Section: Discussionsupporting
confidence: 91%
“…They were interested in FWGS for diseases that develop shortly after birth or during childhood and that are preventable or treatable. Our findings resonate with those from other studies showing that participants were favorable towards testing for childhood-onset conditions, whether or not performed through FWGS [21,[34][35][36].…”
Section: Discussionsupporting
confidence: 91%
“…Our survey findings related to support for NIPT for both preventable and non-preventable AOCs differ from other studies, which have generally shown lower parental support for NIPT for AOCs 30–33. This finding might suggest that this sample places significant value in reproductive autonomy and recognises the benefits that this testing could yield for parents and the family unit.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding attitudes toward NIPT, most women who participated were in favour of NIPT, as recorded in previous studies, 9,10,12,13,15 and thought that it should be available to all women of advanced maternal age in view of the heightened risk of having a child with Down syndrome. Some women also stated that it should be offered to all women regardless of age.…”
Section: Discussionmentioning
confidence: 88%
“…[6][7][8] Because NIPT is an emerging screening method, the attitudes of women and families have been studied across several countries. [9][10][11][12][13][14][15][16] Women have been generally favourable of NIPT across different countries-51% in the Netherlands, 13 74% in Sweden, 9 and 88% in the United Kingdom 15 -even if they had not heard of the test before. 9 Women thought that the most important attribute of NIPT was the safety of the foetus.…”
Section: Introductionmentioning
confidence: 99%